Uji Aktivitas Antiplatelet, Antikoagulan, dan Trombolitik Alkaloid Total Daun Pepaya (Carica papaya L.) secara in Vitro - Rohmah, Martina Kurnia; Fickri, Djelang Zainuddin (Fakultas Farmasi Universitas Andalas, 2020)
Papaya leaves have a number of alkaloid compounds (carpaine, pseudocarpaine, dehydrocarpaine I, dehydrocarpaine II, and emetine). This study aimed to determine the antiplatelet, anticoagulant, and thrombolytic activities of total alkaloids of papaya leaves in vitro. This study was divided into 5 groups: negative control, positive control, and total alkaloids of papaya leaves (0.5, 1.0, and 2.0 mg/mL) with 5 parameters: % platelet aggregation inhibition, CT, PT, APTT, and % thrombolytic. Based on statistical analysis, there was a significant difference between percentage of aggregation inhibition of total alkaloids and negative controls, but was not different with positive control (clopidogrel). Anticoagulant test showed that total alkaloid of papaya leaves significantly extended CT, PT, and APTT values compared with negative control, but was not significantly different with positive control (heparin). Thrombolytic test showed that total alkaloid of papaya leaves increased trombolitic percentage and significantly different from the negative control, but was not significantly different from positive control (nattokinase).